Evaluation of lateral flow assay as a field test for sero-diagnosis of bovine brucellosis - KATHIRIYA, JAYSUKH B; SHAH, NALINKANT M; TRANGADIA, BHAVESH J; BHEDI, KIRIT R; SINDHI, SAMIULLAKHAN H; MONTAGNARO, SERENA (The Indian Journal of Animal Sciences, 2022)
Indirect-ELISA offers a significant advantage over conventional serological methods in the diagnosis of brucellosis in endemic geographical region. Considering iELISA as a gold standard test, RBPT was more sensitive than LFA and the concordance of iELISA with LFA was comparable. The Lateral flow assay is a rapid point-of - care diagnostic test which makes it ideal for use in resource pour countries. It is an immuno-assay and is used also for diagnosis of bovine brucellosis. It is a highly sensitive and specific test which does not require expensive equipment, electricity and or refrigeration or special training. The LFA has shown good PPV (positive predictive value) and NPV (negative predictive value) greater than RBPT in the current study suggest that the test is a simple, cost-effective and rapid that provides accurate detection of antibodies to B. abortus in bovine serum samples, thereby saving time and eliminating the need for special training. It could be used conveniently on the field even in farms located in remote areas. However, evaluation on large sample size would be required for future use. Hence, looking to the results obtained in the present study and by other workers, it is recommended that this rapid test can therefore be practically implemented in serological screening for bovine brucellosis, although evaluation on a larger scale with various sera, and blood samples is still necessary.